Comparative research on creativity in juniors' motivation structure - Popovych, I.; Unhurian, N.; Varnava, U.; Bilosevych, I.; Soroka, O.; Dobrovolska, N.; Hoian, I. (Journal of Physical Education and Sport, 2025)
The aim of this study was to perform theoretical-empirical research into the psychological parameters of creativity within the motivation structure of junior athletes and to compare the findings by gender and sport.